Faszination, Irritation und ästhetischer Eigensinn. Zu einer Geschichte der Interpretationen von Hölderlins «Hälfte des Lebens» (Studia theodisca, 2025)
Since its first printing, Hölderlin’s probably most famous poem Hälfte des Lebens has challenged its recipients. The history of interpretation and the interpretative offers concerning the title and the blank space between the two stanzas not only offer different concepts of meaning, but also sketch a changed understanding of Hölderlin’s authorship, showing that Hölderlin’s text still forces us to think about what constitutes modern poetry.